Efficacy of dietary polyphenol supplement in patients with non-alcoholic fatty liver disease: a network meta-analysis - Wang, Xiao-cui; Song, Li; Wang, Xin-han (Frontiers in Nutrition, 2025)
BackgroundNon-alcoholic fatty liver disease (NAFLD) has become a public health issue worldwide. Dietary polyphenols are naturally occurring plant active ingredients and are widely employed in the treatment of NAFLD. However, the therapeutic effect is still controversial. In this study, a network meta-analysis (NMA) was performed to appraise the effects of various polyphenols on metabolic indices of NAFLD.MethodsPubMed, Embase, the Cochrane Library, and Web of Science were retrieved for English studies on dietary polyphenols in the treatment of NAFLD. Outcome measures were extracted from the included studies and compared using a Bayesian NMA model, encompassing body mass index (BMI), alanine aminotransferase (ALT), aspartate aminotransferase (AST), triglycerides (TG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and necrosis factor alpha (TNF-α).ResultsIn total, 54 randomized controlled trials (RCTs) were included in this study, including 3,132 participants. It involved 13 single (or combined) dietary polyphenols. Naringenin could reduce serum TC (surface under the cumulative ranking curve: 94.59%) and TG (99.00%) in NAFLD patients. Catechin could decrease BMI (77.74%) and serum ALT (94.21%), AST (93.56%), TC (92.26%), and increase HDL-C (93.72%). Dihydromyricetin (DHM) was effective in reducing serum LDL-C (73.22%), and quercetin decreased serum TNF-α (99.47%).ConclusionCatechin may be the most appropriate dietary polyphenol supplement for NAFLD. Future studies should incorporate more RCTs to further validate the efficacy of dietary polyphenols (like DHM and quercetin), which are limited in sample sizes, in treating NAFLD. On the other hand, it is essential to investigate improvements in the bioavailability of these dietary polyphenols and to clarify their safety profiles.